A comparative study of aerosol microphysical properties retrieved from ground-based remote sensing and aircraft in situ measurements during a Saharan dust event - M. J. Granados-Muñoz; J. A. Bravo-Aranda; D. Baumgardner; J. L. Guerrero-Rascado; D. Pérez-Ramírez; F. Navas-Guzmán; I. Veselovskii; H. Lyamani; A. Valenzuela; F. J. Olmo; G. Titos; J. Andrey; et al. (Atmospheric Measurement Techniques, 2016)
In this work we present an analysis of aerosol microphysical properties during a mineral dust event taking advantage of the combination of different state-of-the-art retrieval techniques applied to active and passive remote sensing measurements and the evaluation of some of those techniques using independent data acquired from in situ aircraft measurements. Data were collected in a field campaign performed during a mineral dust outbreak at the Granada, Spain, experimental site (37.16° N, 3.61° W, 680 m a.s.l.) on 27 June 2011. Column-integrated properties are provided by sun- and star-photometry, which allows for a continuous evaluation of the mineral dust optical properties during both day and nighttime. Both the linear estimation and AERONET (Aerosol Robotic Network) inversion algorithms are applied for the retrieval of the column-integrated microphysical particle properties. In addition, vertically resolved microphysical properties are obtained from a multi-wavelength Raman lidar system included in EARLINET (European Aerosol Research Lidar Network), by using both LIRIC (Lidar Radiometer Inversion Code) algorithm during daytime and an algorithm applied to the Raman measurements based on the regularization technique during nighttime. LIRIC retrievals reveal the presence of dust layers between 3 and 5 km a.s.l. with volume concentrations of the coarse spheroid mode up to 60 µm3 cm−3. The combined use of the regularization and LIRIC methods reveals the night-to-day evolution of the vertical structure of the mineral dust microphysical properties and offers complementary information to that from column-integrated variables retrieved from passive remote sensing. Additionally, lidar depolarization profiles and LIRIC retrieved volume concentration are compared with aircraft in situ measurements. This study presents for the first time a comparison of the total volume concentration retrieved with LIRIC with independent in situ measurements, obtaining agreement within the estimated uncertainties for both methods and quite good agreement for the vertical distribution of the aerosol layers. Regarding the depolarization, the first published data set of the CAS-POL for polarization ratios is presented here and qualitatively compared with the lidar technique.